Reversible Data Hiding Using Two Marked Images Based on Adaptive Coefficient-Shifting Algorithm. (4th December 2012) - Yang, Ching-Yu
Abstract : This paper proposes a novel form of reversible data hiding using two marked images by employing the adaptive coefficient-shifting (ACS) algorithm. The proposed ACS algorithm consists of three parts: the minimum-preserved scheme, the minimum-preserved with squeezing scheme, and the base-value embedding scheme. More specifically, each input block of a host image can be encoded to two stego-blocks according to three predetermined rules by the above three schemes. Simulations validate that the proposed method not only completely recovers the host medium but also losslessly extracts the hidden message. The proposed method can handle various kinds of images without any occurrence of overflow/underflow. Moreover, the payload and peak signal-to-noise ratio (PSNR) performance of the proposed method is superior to that of the conventional invertible data hiding schemes. Furthermore, the number of shadows required by the proposed method is less than that required by the approaches which are based upon secret image sharing with reversible steganography.